Linking Product Line Strategies to Competitive Advantage: An Empirical Study of Nigerian Food and Beverages Industry - Ismaila Abubakar; Haruna Isa Mohammad (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose-This study examines the relationships between product line strategies and competitive advantage in Nigerian foods and beverages industry. Design/Methodology-Data were obtained from a sample of 278 employees choosing from 8 companies in the foods and beverages industry located in north-eastern Nigeria using a self-administered questionnaire. Pearson's correlation and Multiple regression were conducted in the data analysis. Findings-Findings of the research revealed that all four hypotheses were supported signifying that product line strategies have significant effects on the competitive advantage of foods and beverages companies in Nigeria. Practical Implications-The study combined the dimensions of product line strategies to determine optimal product line in the food and beverages industry. It provides the decision makers of food and beverages firms in Nigeria with a guide for determining the blend of product line strategies to adopt in order to gain competitive advantage. It also served as a guide to potential investors in the food and beverages industry to make an informed decision that can strategically improve the efficiency and effectiveness through its advocacy on reforming product line strategies.